Pengaruh Komposisi Limbah Kulit Kopi Arabika Gayo Dan Serbuk Kayu Terhadap Sifat Fisik Dan Mekanik Papan Komposit - Futri Habibah Afriandani; M. Jamil; Maizuar; Said Jalalul Akbar; Burhanuddin (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2022)
Composite board is a raw material physically and chemically. The main elements on the composite board in this study are sawdust, horn skins of Gayo Arabica coffee, and adhesives. Comparison of sawdust and coffee mixture in percentage are, 70 : 30, 50 : 50, and 60 : 40. The purpose of this study is to determine the effect of the composition. This method of manufacturing composite boards refers to SNI 03-2105-2006. Therefore, the results obtained for each test that are high at a moisture content of 70:30 with a value of 9.786%, a density of 30 : 70 with a value of 0.59%, a thick development of 70 : 30 with a value of 9%, a biodegradable of 60:40 with a value of 24.20%, a MOE ratio of 30 : 70 with a value of 1378.76 kgf/cm2, MOR 60 : 40 with a value of 657.26 kgf/cm2, tensile Strength of 50 : 50 which is 307,647 kgf/cm2. It is found that the comparison of Gayo Arabica coffee skin and sawdust affects its physical and mechanical properties. The more sawdust on the mixture, the higher the value of its physical properties. The more coffee skins in the mixture, the higher the value of its mechanical properties.